Dynamic Responses of Cylindrical Whispering Gallery Mode Revealed by Axial Liquid Disturbance - Hongchun Zhao; Yue Wang; Yihui Wu (IEEE Photonics Journal)
Cylindrical whispering gallery mode (WGM) microresonators have achieved much attention in the sensing field due to high sensitivity, compatibility and integration. The excitation of spiral modes in such a resonator is unavoidable, causing the axial field distribution, and the injected analytes will undoubtedly interact with the axial mode field, resulting in unclear spectral responses. Here, these responses of the cylindrical WGM are investigated experimentally and theoretically for the first time. Using an optical fiber as the resonator, the experiment is performed by introducing the liquid into a part of the evanescent field along the axis. The perturbation is attributed to the modification of the resonator's profile, leading to an increase of the effective slope. We find the experimental demonstrations of the short-wavelength oscillations of spectral line shapes and the blue shifts of resonant wavelengths. Theoretical studies are consistent with the experimental phenomena. The research in the responses to the axial perturbation provides valuable insights into the effect of spiral modes on cylindrical WGMs and a potentially powerful tool for real-time biochemical analysis.